Functional Characterization of Dma1 and Dma2, the Budding Yeast Homologues of Schizosaccharomyces pombe Dma1 and Human Chfr - Fraschini, Roberta (The American Society for Cell Biology, 2004)
Proper transmission of genetic information requires correct assembly and positioning of the mitotic spindle, responsible for driving each set of sister chromatids to the two daughter cells, followed by cytokinesis. In case of altered spindle orientation, the spindle position checkpoint inhibits Tem1-dependent activation of the mitotic exit network (MEN), thus delaying mitotic exit and cytokinesis until errors are corrected. We report a functional analysis of two previously uncharacterized budding yeast proteins, Dma1 and Dma2, 58% identical to each other and homologous to human Chfr and Schizosaccharomyces pombe Dma1, both of which have been previously implicated in mitotic checkpoints. We show that Dma1 and Dma2 are involved in proper spindle positioning, likely regulating septin ring deposition at the bud neck. DMA2 overexpression causes defects in septin ring disassembly at the end of mitosis and in cytokinesis. The latter defects can be rescued by either eliminating the spindle position checkpoint protein Bub2 or overproducing its target, Tem1, both leading to MEN hyperactivation. In addition, dma1Δ dma2Δ cells fail to activate the spindle position checkpoint in response to the lack of dynein, whereas ectopic expression of DMA2 prevents unscheduled mitotic exit of spindle checkpoint mutants treated with microtubule-depolymerizing drugs. Although their primary functions remain to be defined, our data suggest that Dma1 and Dma2 might be required to ensure timely MEN activation in telophase.